Pengaruh Kualitas Layanan Dan Promosi Penjualan Terhadap Keputusan Pembelian Konsumen Kromosom 78 Cafe - Rusliana, Selvia Naca; Mashadi, Mashadi (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
The coffee shop business that is growing very rapidly lately has also made competition to continue to increase. So that requires every coffee shop owner to pay attention and balance every need and desire of consumers in order to create satisfaction and trust. Service quality and sales promotion is one of the factors that can influence purchasing decisions. The purpose of this study was to determine the effect of each indicator (1) Service Quality on Purchasing Decisions (Study at Kromosom 78 Cafe in Bogor City). (2) Sales Promotion on Purchasing Decisions (Study at Kromosom 78 Cafe in Bogor City). (3) to determine how the Effect of Service Quality and Sales Promotion together on Purchasing Decisions (Study at Kromosom 78 Cafe in Bogor City). This study uses quantitative methods and data collection is carried out by distributing online questionnaires to visitors to the Kromosom cafe, with a total sample of 150 people. With the analysis technique using multiple regression analysis processed with the Statistical Package for the Social Sciences (SPPS 23) program. The results obtained from this study are as follows: (1) Service quality has a positive and significant effect on Purchasing Decisions at Kromosom 78 Cafe with a regression coefficient value of 0.028 and a significant value of 0.000. (2) Sales Promotion has a positive and significant effect on Purchasing Decisions at Kromosom 78 Cafe with a regression coefficient value of 0.845 and has a significance value of 0.000. (3) Service Quality and Sales Promotion have a positive and significant effect on Purchasing Decisions at Kromosom 78 Cafe with an F value of 165.165 and greater than the F table value of 3.06 with a significance value of 0.000.